2019
DOI: 10.3390/cancers11050683
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytomas and Paragangliomas: Bypassing Cellular Respiration

Abstract: Pheochromocytomas and paragangliomas (PPGL) are rare neuroendocrine tumors that show the highest heritability of all human neoplasms and represent a paradoxical example of genetic heterogeneity. Amongst the elevated number of genes involved in the hereditary predisposition to the disease (at least nineteen) there are eleven tricarboxylic acid (TCA) cycle-related genes, some of which are also involved in the development of congenital recessive neurological disorders and other cancers such as cutaneous and uteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 147 publications
(194 reference statements)
0
30
0
Order By: Relevance
“…Our results revealed that patients under 30 had a high germline variant rate (52.6%), suggesting that it is necessary to screen the genes in young patients. On the other hand, with SDHA and SDHD variants, corresponding tumors tend to affect elderly patients (23). It has been reported that the SDHD variant carrier had a penetrance rate of 86% at the age of 50 (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that patients under 30 had a high germline variant rate (52.6%), suggesting that it is necessary to screen the genes in young patients. On the other hand, with SDHA and SDHD variants, corresponding tumors tend to affect elderly patients (23). It has been reported that the SDHD variant carrier had a penetrance rate of 86% at the age of 50 (22,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the dual role of SDH in the TCA-cycle and in mitochondrial electron transport, SDH subunit mutations cause dysfunction of oxidative phosphorylation and hence increased production of reactive oxygen species (ROS), severely affecting cellular energy metabolism (Cascon et al 2019, Moosavi et al 2020. On the other hand, increased tissue succinate levels determined in SDH-related PPGLs (Pollard et al 2005, Rao et al 2013, Richter et al 2014 act as an oncometabolite with broad cellular effects.…”
Section: Introductionmentioning
confidence: 99%
“…The Warburg effect entails a shift of metabolism from oxidative phosphorylation to aerobic glycolysis, as exemplified in PPGL by increased lactate dehydrogenase (LDHA) expression and increased blood lactate levels (Gimenez-Roqueplo et al 2002, Favier et al 2009, Frezza et al 2011. Other pathophysiological mechanisms proposed to play a role in succinate-dependent tumorigenesis are epigenetic dysregulation via altered DNA and histone methylation profiles (Cascon et al 2019), and decreased DNA repair via suppression of the homologous recombination pathway (Sulkowski et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is a kind of human tumor model that has inherited mutations in a metabolic enzyme gene, succinate dehydrogenase subunit D (SDHD). In addition to classic mutations in the genes encoding for the subunits of SDH, in the past five years more germline or somatic mutations have been found in genes encoding for other enzymes catalyzing pivotal steps of the tricarboxylic cycle acid (TCA), such as fumarate hydratase (FH), malate dehydrogenase 2 (MDH2), glutamic-oxaloacetic transaminase 2 (GOT2), and dihydrolipoamide S-succinyltransferase (DLST), in PCC/PGL 9. In regard to the molecular pathogenetic mechanism of PCC/PGL, the hypoxia-related signal pathway (Figure 1) and the increased kinase signal pathways (Figure 2) are two main pathways involving the tumor 10.…”
Section: Introductionmentioning
confidence: 99%